POTENSI BIOSUPLEMEN SINBIOTIK DALAM SOYGURT SEBAGAI TERAPI ADJUVAN PADA PASIEN NEFROPATI DIABETIK - ratna krismondani (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Currently the prevalence of type 2 diabetes mellitus (DM) worldwide reaches a pandemic proportion that affects more than 8% of the global population (nearly over 350 million people) and will increase to more than 550 million people by 2035. Persistent hyperglycemia in diabetic mellitus patients can develop into a chronic kidney disease called diabetic nephropathy. It is estimated that 25% to 40% of diabetic mellitus patients will develop into diabetic nephropathy progressively after 15 years of the duration of the disease and 20% of diabetic nephropathy patients will develop into end stage kidney disease (ESKD) that requires organ transpalanation or dialysis. Therapeutic interventions given to DM patients with diabetic nephropathy have not been able to prevent the progressiveness of renal damage. Recent research has found the potential of soygurt synbiotic biosuplemen as a potential adjuvant therapy for diabetic nephropathy patients. Discussion: Soygurt is a biosuplemen derived from fermented soy milk. Its potential as adjuvant therapy in diabetic nephropathy patients through two mechanisms is a direct and indirect mechanism. In direct mechanisms useful in repairing and preventing kidney damage by acting as an antioxidant, inhibiting the release of inflammatory mediators and blood coagulation factors, as well as improving and inhibiting the occurrence of fibrosis in the kidneys. While indirect mechanisms are useful in lowering risk factors for complications of diabetes mellitus in the kidneys such as obesity, insulin resistance, hyperglycemic, hypertension and dyslipidemia. Conclusion: Soygurt synbiotic biosuplemen have great potential in preventing progressiveity and improving risk factors for kidney damage in diabetic nephropathy patients.